REPRESENTASI LIQUID RELIGION KELAS MENENGAH MUSLIM DALAM FILM ISLAMI PASCA ORDE BARU - Supriansyah, Supriansyah (Khazanah: Jurnal Studi Islam dan Humaniora, 2019)
The main focus of this article is the construction of the middle class Muslims through representation and images in the form of Islamic films. Representations and simulations are used to maintain and strengthen the position of the middle class in Muslim societies. In the era of liberal capitalism, spectacle media is the most popular medium of society. The image is the main value in the media, which disturbs the society of capitalism to smooth the agenda of capitalism and consumerism. The main question in this article is how the representation and simulation of Islam is from the middle class Muslims in Indonesian Islamic films in post-new Order era? This article reveals the position of Islamic films as a medium of preservation of the religious values of the middle class that are displayed through film framing such as economic ability, education qualifications and political choice. The identity of the middle class is a value that is not only illustrated without ideological battles and the struggle for space in films, but at the same time becomes a religious ideological medium, especially the closed middle class Muslims ideology.